Glutamine-Induced Secretion of Intestinal Secretory Immunoglobulin A: A Mechanistic Perspective - Ren, Wenkai; Wang, Kai; Yin, Jie; Chen, Shuai; Liu, Gang; Tan, Bie; Wu, Guoyao; Bazer, Fuller W.; Peng, Yuanyi; Yin, Yulong (Frontiers in Immunology, 2016)
Secretory immunoglobulin A (SIgA) is one important line of defense in the intestinal mucosal surface to protect the intestinal epithelium from enteric toxins and pathogenic microorganisms. Multiple factors, such as intestinal microbiota, intestinal cytokines, and nutrients are highly involved in production of SIgA in the intestine. Recently, glutamine has been shown to affect intestinal SIgA production; however, the underlying mechanism by which glutamine stimulates secretion of intestinal SIgA is unknown. Here, we review current knowledge regarding glutamine in intestinal immunity and show that glutamine-enhanced secretion of SIgA in the intestine may involve intestinal microbiota, intestinal antigen sampling and presentation, induction pathways for SIgA production by plasma cells (both T-dependent and T-independent pathway), and even transport of SIgA. Altogether, the glutamine-intestinal SIgA axis has broad therapeutic implications for intestinal SIgA-associated diseases, such as celiac disease, allergies, and inflammatory bowel disease.